Environment and Wildlife Conservation in Gujarat State a Status Paper - Java, R. L. (Indian Forester, 1991)
The status of wildlife and environment conservation in Gujarat State is detailed in this paper. Wildlife conservation measures/steps to involve the people are also outlined. Details of important National Parks and Wildlife Sanctuaries in Gujarat have been given along with periodic wildlife census data.